CXCL10 induces the recruitment of monocyte-derived macrophages into kidney, which aggravate puromycin aminonucleoside nephrosis. (14th April 2015) - Petrovic-Djergovic, D; Popovic, M; Chittiprol, S; Cortado, H; Ransom, R F; Partida-Sánchez, S
Summary: The mechanism responsible for trafficking of monocyte-derived macrophages into kidney in the puromycin aminonucleoside model of nephrotic syndrome in rats (PAN-NS), and the significance of this infiltration, remain largely unknown. CXCL10, a chemokine secreted in many T helper type 1 (Th1) inflammatory diseases, exhibits important roles in trafficking of monocytes and activated T cells. We hypothesized that induction of circulating interferon (IFN)-γ and glomerular tumour necrosis factor (TNF)-α during PAN-NS would stimulate the release of CXCL10 by podocytes, leading to infiltration of activated immune cells and greater glomerular injury. We found that serum IFN-γ, glomerular Cxcl10  mRNA and intra- and peri-glomerular macrophage infiltration were induced strongly during the late acute phase of PAN-NS in Wistar rats, but not in nude ( Foxn1 rnu/rnu ) rats lacking functional effector T lymphocytes. Wistar rats also developed significantly greater proteinuria than nude rats, which could be abolished by macrophage depletion. Stimulation of cultured podocytes with both IFN-γ and TNF-α markedly induced the expression of Cxcl10  mRNA and CXCL10 secretion. Together, these data support our hypothesis that increased circulating IFN-γ and glomerular TNF-α induce synergistically the production and secretion of CXCL10 by podocytes, attracting activated macrophages into kidney tissue. The study also suggests that IFN-γ, secreted from Th1 lymphocytes, may prime proinflammatory macrophages that consequently aggravate renal injury.